2017
DOI: 10.1101/168245
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Overexpression of Channelrhodopsin 2 interferes with the GABAb receptor-mediated depression of GABA release from the somatostatin-containing interneurons of the prefrontal cortex

Abstract: Region and cell-type restricted expression of light activated ion channels is the indispensable tool to study properties of synapses in specific circuits and to monitor synaptic alterations by various stimuli including neuromodulators and behaviors, both ex vivo and in vivo. These analyses require the light-activated proteins or viral vectors for their delivery that do not interfere with the phenomenon under study. Here, we report a case of such interference in which the high-level expression of Channelrhodops… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
(17 reference statements)
1
2
0
Order By: Relevance
“…These accumulations were not considered somatic staining and therefore not included in the quantification. A similar phenomenon has been observed by other groups following viral overexpression of ChR2-eYFP ( Figure 1 B in 60 ).…”
Section: Methodssupporting
confidence: 89%
“…These accumulations were not considered somatic staining and therefore not included in the quantification. A similar phenomenon has been observed by other groups following viral overexpression of ChR2-eYFP ( Figure 1 B in 60 ).…”
Section: Methodssupporting
confidence: 89%
“…Several reports indicated that expressing heterologous proteins, for example Channelrhodopsin (ChR2) 12 , may change network homeostasis 45 . To test whether we can observe this in our system, we compared development changes in neuronal activity in neurons expressing the microbial opsin CatCh to those that did not express any heterologous protein.…”
Section: Resultsmentioning
confidence: 99%
“…A note of caution that we feel compelled to point out is that our investigations rely heavily on an overexpression system, which has been shown in published studies to yield artifactual results [26][27][28][29][30][31] and likely also observed in many unpublished works. We used the same lentiviral vector to overexpress other genes in KPL cells, including a catalytically dead Cas9 (dCas9), and found that regardless of the gene, overexpression appeared to increase tumor burden in vivo, compared to vector control (data not shown).…”
Section: Markosyan Et Al Observed a Decrease In Tumor Cell Proliferation And In Vivo Tumor Burden Withmentioning
confidence: 98%